2010
DOI: 10.1021/nl1013663
|View full text |Cite
|
Sign up to set email alerts
|

Broadband Absorbing Bulk Heterojunction Photovoltaics Using Low-Bandgap Solution-Processed Quantum Dots

Abstract: We describe bulk heterojunction (BHJ) solar cells containing blends of colloidal PbS nanocrystal quantum dots with several new donor-acceptor conjugated polymers. Using photoinduced absorption spectroscopy we found that blends of PbS quantum dots with one polymer, poly(2,3-didecyl-quinoxaline-5,8-diyl-alt-N-octyldithieno[3,2-b:2',3'-d]pyrrole) (PDTPQx), produce significantly more photoinduced charge than blends of PbS with the other donor-acceptor polymers or with traditionally studied polymers like [2-methoxy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
132
1

Year Published

2011
2011
2017
2017

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 123 publications
(139 citation statements)
references
References 41 publications
(82 reference statements)
5
132
1
Order By: Relevance
“…We presume that the V oc can be attributed to the energy difference between the HOMO of P3HT and LUMO of PCBM in our standard cell as it has been reported by other research groups [42][43][44][45][46][47]. Since the value of conduction band of PbS-QDs is consistently aligned with the LUMO value of PCBM [1,14,28] as shown in Figure 7, therefore it is obvious that the V oc of hybrid device -I is consistent with the standard P3HT:PCBM devices. This explains the charge transfer takes place at P3HT/PCBM interface in the case of standard devices, whereas the same phenomenon of charge transfer occurs at the interface(s) of P3HT/PbS and/or P3HT/(PCBM/PbS) in case of the hybrid devices.…”
Section: -P3supporting
confidence: 76%
See 4 more Smart Citations
“…We presume that the V oc can be attributed to the energy difference between the HOMO of P3HT and LUMO of PCBM in our standard cell as it has been reported by other research groups [42][43][44][45][46][47]. Since the value of conduction band of PbS-QDs is consistently aligned with the LUMO value of PCBM [1,14,28] as shown in Figure 7, therefore it is obvious that the V oc of hybrid device -I is consistent with the standard P3HT:PCBM devices. This explains the charge transfer takes place at P3HT/PCBM interface in the case of standard devices, whereas the same phenomenon of charge transfer occurs at the interface(s) of P3HT/PbS and/or P3HT/(PCBM/PbS) in case of the hybrid devices.…”
Section: -P3supporting
confidence: 76%
“…A schematic illustration is depicted in Figure 7, with all the photoactive materials used in this experiment along with their respective energy levels [1,14,28,31,33,37,38], in order to explain the working mechanism(s). In a ternary nanoblend of (P3HT:PCBM):PbS/MWCNT, it has been reported that there is almost a flat band condition between the LUMO of PCBM and the conduction band of PbS-QDs [14,39] as shown in Figure 7.…”
Section: -P3mentioning
confidence: 99%
See 3 more Smart Citations